2014
DOI: 10.1186/1471-2407-14-819
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 and the clinical outcomes of various carcinomas: a systematic review and meta-analysis

Abstract: BackgroundMicroRNA-21 (miR-21) has been suggested to play a significant role in the prognosis of carcinoma. The recognition of novel biomarkers for the prediction of cancer outcomes is urgently required. However, the potential prognostic value of miR-21 in various types of human malignancy remains controversial. The present meta-analysis summarises and analyses the associations between miR-21 status and overall survival (OS) in a variety of tumours.MethodsEligible published studies were identified by searching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…miR-21 has been reported to be one of the most commonly up-regulated miRNAs in various human cancers functioning as a key regulator of carcinogenic process, and has been considered as a novel target in cancer therapeutics (Selcuklu et al, 2009; Krichevsky and Gabriely, 2009; Pan et al, 2010; Kumarswamy et al, 2011; Wang et al, 2014a). It is interesting that recent studies also show that miR-21 is critically involved in arsenic-induced cell malignant transformation and tumorigenesis.…”
Section: The Role Of Mirnas In Metal Carcinogen-induced Cell Maligmentioning
confidence: 99%
“…miR-21 has been reported to be one of the most commonly up-regulated miRNAs in various human cancers functioning as a key regulator of carcinogenic process, and has been considered as a novel target in cancer therapeutics (Selcuklu et al, 2009; Krichevsky and Gabriely, 2009; Pan et al, 2010; Kumarswamy et al, 2011; Wang et al, 2014a). It is interesting that recent studies also show that miR-21 is critically involved in arsenic-induced cell malignant transformation and tumorigenesis.…”
Section: The Role Of Mirnas In Metal Carcinogen-induced Cell Maligmentioning
confidence: 99%
“…The axis FASLG/miR-21 may also represent an important molecular mechanism in ALPS-FAS pathophysiology, as soluble FASLG is augmented in patients [19]. Moreover, growing evidence from recent studies has shown the involvement of miR-21 in several cancers [20]. Its upregulation, particularly in cancerous tissue, is effectively predictive of worse prognosis in multiple carcinomas [21].…”
Section: T Cell Receptor (Tcr)abmentioning
confidence: 99%
“…The role of miR-21 in several types of cancers is well documented [20]. Due to the apoptotic defect, ALPS patients are prone to develop lymphoma [2].…”
Section: Microrna-21-3p Up-regulation In Alps-fasmentioning
confidence: 99%
“…MiR-21 was described as an oncomiR and implicated in tumor progression of various cancers [1215]. Of interest, up-regulation of miR-21 was associated with lung cancer diagnosis and prognosis, indicating a potential role of miR-21 in human lung cancer progression [16, 17].…”
Section: Introductionmentioning
confidence: 99%